Prevalence of HBsAg and Anti HCV Sero-Positivity among Healthy Bangladeshi Job Seekers in Gulf States and KSA - Ahmed, AZT; Khan, NA; Tofail, FG; Hakim, M; Siddique, MAR (Bangladesh Medical Journal, 2011)
DOI: 10.3329/bmj.v39i2.7035 Bangladesh Medical Journal 2010, 39(2) pp.35-39